Effect of fiber type on the level of stress concentration created by U-notches in long-fiber composite plates - Turgut, A.; Arsian, N.; Sancaktar, Erol (Publ by ASME, 1993)
The effect of fiber type on the level of stress concentration created by u-notches were investigated for unidirectional and symmetric cross-ply laminates loaded on or off-axis. The finite element method was used for this purpose utilizing triangular elements under plane stress conditions. Analyses were performed for three different fiber reinforcements of epoxy matrix: glass, graphite and boron. Typical material properties reported in the literature for glass/epoxy, boron/epoxy and graphite/epoxy were used in calculations. The accuracy of the finite element code utilized was first checked by calculating the u-notch stress concentration factors for an isotropic steel plate.
14th Biennial Conference on Mechanical Vibration and Noise -- 19 September 1993 through 22 September 1993 -- Albuquerque, NM, USA -- 19400
Keywords: Boron; Composite materials; Epoxy resins; Fiber reinforced materials; Finite element method; Glass; Graphite; Laminates; Stress analysis; U-notches; Plates (structural components)